PENGARUH EARNING MANAGEMENT, INTENSITAS ASET TETAP DAN KONSERVATISME AKUNTANSI TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) SELAMA PERIODE TAHUN 2017 – TAHUN 2022 - Hamdani; Mulyani, Nani (Jurnal Nusa Akuntansi, 2025)
This research aims to analyze the influence of Earning Management, Fixed Asset Intensity, and Accounting Conservatism on Tax Avoidance with Company Size as a Moderating Variable. This research was conducted by analyzing the financial reports of companies in the property sector listed on the Indonesia Stock Exchange (BEI) during the period 2017 to 2022. The sample used in this research was 12 property sector companies listed on the Indonesia Stock Exchange during the period. 2017 to 2022 using purposive sampling techniques. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The panel data regression method was used as the research methodology in this study. Analysis of research results using e-views version 9. The results of this study show that Earning Management, Fixed Asset Intensity, and Accounting Conservatism have an effect on Tax Avoidance, Earning Management has no effect on Tax Avoidance, Fixed Asset Intensity has an effect on Tax Avoidance, Accounting Conservatism has an effect on Tax Avoidance, Company Size does not moderate the effect of Earnings Management on Tax Avoidance, Company Size does not moderate the influence of Fixed Asset Intensity on Tax Avoidance, Company Size moderates the influence of Accounting Conservatism on Tax Avoidance